Analisis Kepatuhan Asersi Partai Politik X terkait Laporan Penerimaan dan Pengeluaran Dana Kampanye atas Audit Laporan Dana Kampanye Pemilu Legislatif 2024 (Studi Kasus pada KAP LMR) - Mohammad Mirza Rafiudin; Sjarief Hidajat (ITB AAS INDONESIA, 2024)
The purpose of this study is to analyze the compliance of assertions from Political Party X related to the Campaign Fund Receipt and Expenditure Report on the audit of the 2024 legislative election campaign fund report conducted by KAP Luthfi Muhammad & Rekan. The research methodology used is a qualitative approach, utilizing primary data collected through interview procedures and secondary data obtained through documentation techniques. The scope of this research focuses on analyzing the compliance of assertions in the Campaign Fund Receipt and Expenditure Report (LPPDK) with campaign finance regulations, namely Peraturan KPU No. 18 Tahun 2023. The results of this study indicate that, of the 8 assertions contained in the LPPDK, assertion 1 regarding the content of LPPDK information is the assertion with the highest percentage violated by 7 districts/cities from Political Party X, which is 23% and there is 1 district/city that does not report LPPDK so that it is declared non-compliant with all LPPDK assertions. Then, the assertions with the lowest percentage that were violated by the district/city of Political Party X were assertion 6 regarding the limitation/suitability of donations and assertion 7 regarding prohibited donations.